Causality of Financial Literacy and Non-Financial Information to Investment Decisions (Experimental Study) - Alfiyan, Ahmad; Abdani, Fadlil (E-Jurnal Akuntansi, 2023)
The Covid-19 outbreak has hit various sectors of the economy, such as the capital market. The decline in IHSG made the number of investors increase to 15.96%. However, the increase in the number of investors is not supported by good financial literacy and sufficient non-financial information. If it is associated with signal theory, a person will react when he hears certain information that has an impact on his investment decisions. The purpose of this study is to test the main effect and interaction effect of financial literacy variables and non-financial information on investment decisions using experimental study research methods. This study used a factorial pattern of 2 x 2 between-subject and the sample used was 5th semester students. The data analysis technique will use Analysis of Variance (ANOVA) The results of the main effect state that the two variables have an influence on investment decisions while the interaction effect does not occur between the two variables on investment decisions. Keywords: Financial Literacy; Non-Financial Information; Financial Decisions